2007
DOI: 10.1530/eje.1.02351
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical experiences with the role of dopamine receptors in the treatment of pituitary adenomas

Abstract: Pituitary tumors can cause symptoms of mass effect and hormonal hypersecretion that can be reversed with surgical resection or debulking of the adenoma, radiotherapy, or medical treatment. Medical treatment is the primary choice for prolactinomas because dopamine agonists are very effective in the treatment of these tumors, with rates of control (tumor size reduction and hormone suppression) as high as 80-90% for microprolactinomas and 60-75% for macroprolactinomas. The function of dopamine receptors in other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…Recently, bromocriptine and cabergoline have been shown to be effective in suppressing ACTH secretion in a small group of patients with lung carcinoid (Reith et al 1987, Pivonello et al 2007a, as previously observed in vitro by Farrell et al (1992). Moreover, preliminary data by Pivonello et al (2008) demonstrated an in vitro inhibitory effect of cabergoline on cell growth in ten different cases of pancreatic endocrine tumors (seven cases defined as well-differentiated tumors and three defined as well-differentiated carcinomas).…”
Section: Ss and Da Analogs Treatment In Endocrine Tumorssupporting
confidence: 59%
See 3 more Smart Citations
“…Recently, bromocriptine and cabergoline have been shown to be effective in suppressing ACTH secretion in a small group of patients with lung carcinoid (Reith et al 1987, Pivonello et al 2007a, as previously observed in vitro by Farrell et al (1992). Moreover, preliminary data by Pivonello et al (2008) demonstrated an in vitro inhibitory effect of cabergoline on cell growth in ten different cases of pancreatic endocrine tumors (seven cases defined as well-differentiated tumors and three defined as well-differentiated carcinomas).…”
Section: Ss and Da Analogs Treatment In Endocrine Tumorssupporting
confidence: 59%
“…Beyond the above-mentioned NET, the presence of DR -mainly D 2 -has been demonstrated in a small group of well-differentiated endocrine tumors (including lung and thymic carcinoids), associated with ectopic ACTH secretion and Cushing's syndrome (Pivonello et al 2007a).…”
Section: Dr Expression In Endocrine Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the chimeric molecules acting simultaneously on somatostatin 2A and dopamine D2 receptors were developed and their enhanced potency in inhibiting both growth hormone and prolactin secretion was shown [9]. These compounds were also found to suppress in vitro the viability of cells isolated from the clinically nonfunctioning pituitary adenomas and were suggested as potential future medical treatment for this type of malignancies [8,10].…”
Section: Introductionmentioning
confidence: 99%